Creativity and the 8 key-competences: the skills needed for a modernising world - Petru Valentin DIACONU (Acta et Commentationes, Sciences of Education, 2026)
The world in which we live today is continuously changing, maybe now more than ever. Three decades ago, in similar contexts, the idea of transversal competences that may offer flexibility to the citizens came into being. Later on, as it was adopted the European Union, it evolved and was inserted as one of the main points of educational policy, becoming the 8 Key Competences for Life-Long-Learning. As we explore the evolution of the concept and its role in the society of the European Union, especially in our day, one of the conclusions that we reach is the possible role of creativity in gaining the key competencies and using them to their fullest throughout our lives. As the positive effects of creativity interlock with those of the key competences, I dare to think that these concepts can have a beneficial role if used together, be it in the classroom, or outside of it.